The Effectiveness of the Regional Regulation Formation Agency in Producing Initiative Regional Regulations - Deo Jeremy Tulangow; Joanne V. Mangindaan; Very Y. Londa (Borong Newinera Publisher, 2024)
This research aims to analyze the effectiveness of the Regional Regulation Formation Agency in Producing Initiative Regional Regulations in the DPRD of North Sulawesi. This research uses the theory of Richard M. Steers with measures of effectiveness, namely goal achievement, integration and adaptation. This research used a qualitative descriptive method with 4 informants consisting of the deputy chairman of the DPRD of North Sulawesi, the chairman of BAPEMPERDA (Regional Regulation Establishment Agency), members of BAPEMPERDA, and BAPEMPERDA staff. The results of this research show that the performance of BAPEMPERDA is still not optimal, seen from the lack of effectiveness in making regional regulations, to the point that they do not reach directly to the community. Based on research findings, several things that need to be suggested to the DPRD (Regional People's Representative Council), especially BAPEMPERDA North Sulawesi, are the need for commitment from DPRD members so that a regional regulation can be effective, not only in terms of quality, but can be felt by the constituents, namely the community.